2008
DOI: 10.1016/j.physletb.2008.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Quantum tunneling and back reaction

Abstract: Abstract:We give a correction to the tunneling probability by taking into account the back reaction effect to the metric of the black hole spacetime. We then show how this gives rise to the modifications in the semiclassical black hole entropy and Hawking temperature. Finally, we reproduce the familiar logarithmic correction to the Bekenstein-Hawking area law.In 1975, Hawking discovered [1] the remarkable fact that black holes, previously thought to be completely black regions of spacetime from which nothing c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
194
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(205 citation statements)
references
References 21 publications
9
194
1
1
Order By: Relevance
“…Such a structure was obtained earlier [12] in radial null geodesic approach by explicitly taking into account the one loop back reaction effect. Also, as stated earlier, such a form follows from conformal field theory techniques [22] where α is given by (3.26).…”
Section: Jhep06(2008)095supporting
confidence: 60%
See 2 more Smart Citations
“…Such a structure was obtained earlier [12] in radial null geodesic approach by explicitly taking into account the one loop back reaction effect. Also, as stated earlier, such a form follows from conformal field theory techniques [22] where α is given by (3.26).…”
Section: Jhep06(2008)095supporting
confidence: 60%
“…Inspite of some sporadic attemps [10,11] a systemetic, thorough and complete analysis is lacking. In our previous work [12] we found out the corrections to the temperature and entropy by including the effects of back reaction knowing the modified surface gravity of the black hole due to one loop back reaction for the Schwarzschild case by radial null geodesic method. As an extension we [13] also applied this method for a noncommutative Schwarzschild metric.…”
Section: Jhep06(2008)095mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, given the results of [16] and associated works (see [34] and the references therein), Banerjee and Majhi gave an additional tunneling probability correction by considering the back reaction effect of the BH space-time metric [34]. In particular, they demonstrated that a SBH's tunneling probability can be written as [34] …”
Section: Corrections To the Hawking Temperature And Bekensteinhawkingmentioning
confidence: 99%
“…from equation (33) in [34], where = 1/8 is a dimensionless parameter (corresponding to the prefactor −1/2 of the QG calculations) and their revised Hawking temperature is [34] …”
Section: Corrections To the Hawking Temperature And Bekensteinhawkingmentioning
confidence: 99%